Exploring Methemoglobinemia: A Case Presentation Associated with Dapsone Use (Revista de Medicina Clinica, 2025)
Introduction: Methemoglobinemia (MetHb) is the elevation of the blood level of hemoglobin with ferric ion (+3)). Hemoglobin is unable to dissociate from oxygen without being able to deliver it to tissues. The clinical symptoms and plasma metahemoglobin levels guide us in the diagnosis. It can originate congenitally or acquired, characterized mainly by hypoxemia. It can originate congenitally or acquired, characterized mainly by hypoxemia. Case Report: A 22-year-old male with a history of treated pulmonary coccidioidomycosis and pulmonary sequelae from COVID-19. He is currently being treated with dapsone for dermatosis caused by Nocardia asteroides. Three weeks prior to admission, he began experiencing dyspnea with small to moderate exertion, as well as fatigue, weakness, and decreased oxygen saturation to 72%, which was associated with distal cyanosis. This was the reason for his visit to the emergency department. Upon admission, he was found to have refractory hypoxemia despite supplemental oxygen. Laboratory results showed normocytic hypochromic anemia and mixed acidosis on blood gas analysis, with suspected methemoglobinemia due to dapsone use. His methemoglobin levels were 26.6%. Treatment with methylene blue and ascorbic acid was started, resulting in a decrease in methemoglobin levels and clinical improvement Discussion: Methemoglobinemia is a rare entity that may go unnoticed depending on its origin. Having adequate diagnostic tools, the discarding of differential diagnoses and a good history are key to a good diagnostic approach
Keywords: Hypoxia; Cyanosis; Partial Pressure of Oxygen (PO2); Partial Pressure of Carbon Dioxide (PCO2); Metheglobin (MetHb); Daposone